How Mr. Bean Film Influence Student’s Engagement in Learning Tenses - Muthmainnah, Muthmainnah; Ibna Seraj, Prodhan Mahbub Ibna; Al Yakin, Ahmad; Abd Al-Lateef, Ghada Tosson; Esmianti, Farida (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
This research concentrates to analyze student’s engagement in learning English in online environment amid Covid 19. Mr. Bean film used in this study to help students understand English tenses for EFL classroom. A random choice of English subject was made with 21 students from Technique Information of Computer Science faculty at Universitas Al Asyariah Mandar Indonesia. The English tenses content and language level difficulty based on a Mr. Bean film was chosen in teaching were: simple present tense, present continuous, Present perfect, past simple. They looked at the Mr. Bean film, analyze the tenses, re write the tenses in sentences then create their own tenses. After the film, the participants replied to material understanding and questions by retelling on their video. The collected data were subject to descriptive qualitative. The findings showed that Mr. Bean film have a positive effect on English understanding of tenses content. It can be argued that the participants better understand the English tenses with film. In addition, it is found in this study student’s engagement increase and they were motivated to learn English tenses. The teacher's pedagogy is to use a certain Mr. Bean film to enhance the student’s motivation, engagement and help to be easier to understanding tenses.